A nation on trial : the Goldhagen thesis and historical truth - Finkelstein, Norman G.; Birn, Ruth Bettina 1952- (Metropolitan Books, 1998)
In his book, Hitler's Willing Executioner, Daniel Goldhagen maintains that ordinary Germans were driven by fanatical anti-Semitism to murder the Jews. "In A Nation on Trial, two leading critics [Norman G. Finkelstein and Ruth Bettina Birn] challenge Goldhagen's findings". -- Jacket